2004
DOI: 10.1023/b:jarg.0000029495.22787.83
|View full text |Cite
|
Sign up to set email alerts
|

DNA Fragmentation, Mitochondrial Dysfunction and Chromosomal Aneuploidy in the Spermatozoa of Oligoasthenoteratozoospermic Males

Abstract: Purpose : This study determined the incidence of sperm nuclear DNA fragmentation, mitochondrial dysfunction, and chromosomal aneuploidy. The results were correlated with the semen analysis parameters and fertilization rates. Methods : Semen samples from 10 men showing oligoasthenoteratozoospermia (OAT) and undergoing ICSI treatment were analyzed. Another semen samples from 10 men showing normozoospermia and undergoing IVF treatment were analyzed for comparison. The samples were prepared using a two-step discon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
0
3

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(46 citation statements)
references
References 40 publications
2
41
0
3
Order By: Relevance
“…Sperm cryopreservation is wide-ranging clinical application but present procedures are not perfect, and especially semen samples from OAT patients there is an increased vulnerability to cryoinjury [1]. It is also important to demonstrate the ratio of functional sperms after thawing in OAT patients, as it has been reported that sperm from OAT patients have more DNA damage, mitochondrial dysfunction and chromosomal aneuploidy than normospermic men [5]. Extracellular and intracellular ice crystal generation, osmotic shock and cellular dehydration have been reported after freezing and thawing of human sperms [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sperm cryopreservation is wide-ranging clinical application but present procedures are not perfect, and especially semen samples from OAT patients there is an increased vulnerability to cryoinjury [1]. It is also important to demonstrate the ratio of functional sperms after thawing in OAT patients, as it has been reported that sperm from OAT patients have more DNA damage, mitochondrial dysfunction and chromosomal aneuploidy than normospermic men [5]. Extracellular and intracellular ice crystal generation, osmotic shock and cellular dehydration have been reported after freezing and thawing of human sperms [9].…”
Section: Discussionmentioning
confidence: 99%
“…The most significant alterations concerning apoptosis are phosphatidylserine production, DNA fragmentation and the creation of apoptotic structures [3]. Decreased sperm quality, increased DNA fragmentation and mitochondrial dysfunction have been reported in OAT patients [5]. It was also shown that cryopreservationthawing techniques reduced motility, viability and fertilizing ability of sperms in teratospermic patients more than in normospermic men [6].…”
Section: Turan Et Almentioning
confidence: 99%
“…In assisted reproduction programs, several studies show that high levels of sperm DNA fragmentation are related to lower pregnancies rates either natural or using IUI, IVF or ICSI procedures [54][55][56][57] and higher aneuploidies rates in embryos [52,58,59]. Greco et al [60] reported 29 ICSI cycles in which the percentage of DNA-fragmented spermatozoa, detected by TUNEL assay, was >15%; only two pregnancies and no births were obtained.…”
Section: Discussionmentioning
confidence: 99%
“…Reduced semen quality is the main cause of male factor (2-4) and oligoasthenoteratozoospermia (OAT) is the most common diagnosis of abnormal semen quality (2). Several studies have shown that both testicular spermatozoa and poor semen quality are associated with a higher rate of sperm chromosome aneuploidy, improper meiotic recombination (5,6), sperm DNA fragmentation and mitochondrial dysfunction in patients with azoospermia (OA), OAT or severe OAT (7)(8)(9)(10). Although, a recent study indicated that impaired testicular function is reversible with different treatment modalities (11), intracytoplasmic sperm injection (ICSI) using the spermatozoa of these men may result in poor cycle outcome.…”
Section: Introductionmentioning
confidence: 99%